Politiques du paysage et pratiques paysagistes dans la métropole bordelaise (1980-2021) - Chris Pividori (Projets de Paysage)
In recent decades, the landscape has become one of the dimensions and one of the tools in urban planning for large French conurbations. Bordeaux is no exception to the rule since it is an example of the progressive integration of the landscape in public action. There has been a concomitant and increasing diversification in landscape practices. The Bordeaux metropolis thus appears as a good choice for conducting a critical analysis of contemporary landscape practices. The article seeks to define different periods in landscape policies applied at the scale of the conurbation since the 1980s and to study their impacts on the urban fabric. It also seeks to identify the role played by landscape architects and urban planners in this urban fabric. This ongoing doctoral research reveals the close relationship between these two aspects and proposes a critical approach of contemporary landscape practices in the Bordeaux metropolis. It also raises the question of the role granted to landscape architects in this field, and the room to manoeuvre they have had and continue to have.